Berberine Alleviates Amyloid β-Induced Mitochondrial Dysfunction and Synaptic Loss. (2nd May 2019) - Zhao, Chunhui; Su, Ping; Lv, Cui; Guo, Limin; Cao, Guoqiong; Qin, Chunxia; Zhang, Wensheng
Abstract : Synaptic structural and functional damage is a typical pathological feature of Alzheimer's disease (AD). Normal axonal mitochondrial function and transportation are vital to synaptic function and plasticity because they are necessary for maintaining cellular energy supply and regulating calcium and redox signalling as well as synaptic transmission and vesicle release. Amyloid- β (A β ) accumulation is another pathological hallmark of AD that mediates synaptic loss and dysfunction by targeting mitochondria. Therefore, it is important to develop strategies to protect against synaptic mitochondrial damage induced by A β . The present study examined the beneficial effects of berberine, a natural isoquinoline alkaloid extracted from the traditional medicinal plant Coptis chinensis, on A β -induced mitochondrial and synaptic damage in primary cultured hippocampal neurons. We demonstrate that berberine alleviates axonal mitochondrial abnormalities by preserving the mitochondrial membrane potential and preventing decreases in ATP, increasing axonal mitochondrial density and length, and improving mitochondrial motility and trafficking in cultured hippocampal neurons. Although the underlying protective mechanism remains to be elucidated, the data suggest that the effects of berberine were in part related to its potent antioxidant activity. These findings highlight the neuroprotective and specifically mitoprotective effects of berberine treatment under conditions of A β enrichment.